2006
DOI: 10.1158/1055-9965.epi-06-0595
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Colon and Rectal Cancers: The European Prospective Investigation into Cancer and Nutrition

Abstract: We investigated several aspects of the role of physical activity in colon and rectal cancer etiology that remain unclear in the European Prospective Investigation into Nutrition and Cancer. This cohort of 413,044 men and women had 1,094 cases of colon and 599 cases of rectal cancer diagnosed during an average of 6.4 years of follow-up. We analyzed baseline data on occupational, household, and recreational activity to examine associations by type of activity, tumor subsite, body mass index (BMI), and energy int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
150
1
7

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 71 publications
8
150
1
7
Order By: Relevance
“…The results indicate that frequent physical activity at a relatively high intensity level, here categorized as moderate, may reduce the risk of colon cancer. Similar observations have been reported by Friedenreich and colleagues in a large cohort study from the European Prospective Investigation into Cancer and Nutrition (11). They therefore suggest daily activity for at least one hour with intensity at a vigorous level to prevent cancer, which should fit well with the activity pattern in most ball disciplines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results indicate that frequent physical activity at a relatively high intensity level, here categorized as moderate, may reduce the risk of colon cancer. Similar observations have been reported by Friedenreich and colleagues in a large cohort study from the European Prospective Investigation into Cancer and Nutrition (11). They therefore suggest daily activity for at least one hour with intensity at a vigorous level to prevent cancer, which should fit well with the activity pattern in most ball disciplines.…”
Section: Discussionsupporting
confidence: 85%
“…Friedenreich and colleagues discuss the most beneficial type, dose and timing of activity for breast cancer risk. They observed the greatest risk reductions at vigorous intensity levels of recreational activity and conclude that lifetime activity is of major importance (11). Based on their statements, we should at the present expect reduced risk of breast cancer in the females at the high level of lifetime activity as well.…”
Section: Discussionmentioning
confidence: 97%
“…Few cohort studies of physical activity and colon cancer have conducted analyses stratified by tumor sub-site [6,12,13,[16][17][18][32][33][34]36,37,48,49], with those that did yielding conflicting results. Some studies reported stronger inverse findings for the proximal colon [12,16,17,33,48], while others observed stronger inverse associations for distal colon sites [6,13,18,36,37]. Observed differences may be due to varying etiologies between tumors of the proximal and distal colon [50].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the Fukuoka Colorectal Cancer Study showed that job-related as well as total and moderate leisure-time physical activity were associated with a significant reduction of rectal cancer risk in men only [51]. In contrast, several cohort studies [12,17,33] have failed to detect an association between physical activity and rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that have been shown to increase risk of colon cancer include disturbances in energy balance (e.g., physical inactivity and/or obesity) (3)(4)(5), high intake of red or processed meat (6), low folate intake, high alcohol intake, and cigarette smoking (7). In addition, aspirin use (8)(9)(10) and postmenopausal hormone use (11) have also been shown to reduce a woman's risk of colon cancer.…”
mentioning
confidence: 99%